Newborn Metabolic Profile Associated with Hyperbilirubinemia With and Without Kernicterus - Molly E. McCarthy; Scott P. Oltman; Rebecca J. Baer; Kelli K. Ryckman; Elizabeth E. Rogers; Martina A. Steurer‐Muller; John S. Witte; Laura L. Jelliffe‐Pawlowski (Wiley, 2019)
Abstract Our objective was to assess the relationship between hyperbilirubinemia with and without kernicterus and metabolic profile at newborn screening. Included were 1,693,658 infants divided into a training or testing subset in a ratio of 3:1. Forty‐two metabolites were analyzed using logistic regression (odds ratios (ORs), area under the receiver operating characteristic curve (AUC), 95% confidence intervals (CIs)). Several metabolite patterns remained consistent across gestational age groups for hyperbilirubinemia without kernicterus. Thyroid stimulating hormone (TSH) and C‐18:2 were decreased, whereas tyrosine and C‐3 were increased in infants across groupings. Increased C‐3 was also observed for kernicterus (OR: 3.17; 95% CI: 1.18-8.53). Thirty‐one metabolites were associated with hyperbilirubinemia without kernicterus in the training set. Phenylalanine (OR: 1.91; 95% CI: 1.85-1.97), ornithine (OR: 0.76; 95% 0.74-0.77), and isoleucine + leucine (OR: 0.63; 95% CI: 0.61-0.65) were the most strongly associated. This study showed that newborn metabolic function is associated with hyperbilirubinemia with and without kernicterus.